Decreased Endothelial Function and Increased Subclinical Heart Failure in Women Several Years After Pre-eclampsia. Issue 1 (January 2019) - Breetveld, N. M.; Ghossein-Doha, C.; van Neer, J.; Sengers, M. J. J. M.; Geerts, L.; van Kuijk, S. M. J.; van Dijk, A. P.; van der Vlugt, M. J.; Heidema, W. M.; Brunner-la Rocca, H. P.; Scholten, R. R.; Spaanderman, M. E. A.
Abstract : (Abstracted from Ultrasound Obstet Gynecol 2018;52:196–204) Preeclampsia (PE) is associated with both postpartum endothelial dysfunction and asymptomatic structural heart alterations consistent with heart failure stage B (HF-B). This study assessed the relationship between endothelial function, along with components of metabolic syndrome, and asymptomatic structural heart dysfunction in formerly preeclamptic women and healthy parous controls.